Nebulized Bacteriophages for Prophylaxis of Experimental Ventilator-Associated Pneumonia Due to Methicillin-Resistant Staphylococcus aureus. Issue 7 (July 2020) - Prazak, Josef; Valente, Luca; Iten, Manuela; Grandgirard, Denis; Leib, Stephen L.; Jakob, Stephan M.; Haenggi, Matthias; Que, Yok-Ai; Cameron, David R.
Abstract : Objectives: There is a need for alternative strategies to combat and prevent antibiotic-resistant bacterial infections. Here, we assessed the potential for bacteriophage prophylaxis in the context of experimental ventilator-associated pneumonia due to methicillin-resistant Staphylococcus aureus in rats. Design: Nebulized phages (aerophages) were delivered to the lungs of rats using a modified vibrating mesh aerosol drug delivery system. Animals were intubated and ventilated for 4 hours, at which point they were infected with methicillin-resistant S. aureus strain AW7 via the endotracheal tube, extubated, and then monitored for 96 hours. Setting: Ventilator-associated pneumonia. Subjects: Male Wistar rats. Interventions: A single application of aerophages prior to ventilation at one of two concentrations (~1010 plaque forming units/mL or ~1011 plaque forming units/mL). Measurements and Main Results: 1) Animal survival at 96 hours, 2) enumeration of bacteria and phages in the lungs and spleen, and 3) lung tissue histopathology. Animals that received aerophages prior to ventilation and methicillin-resistant S. aureus challenge showed a higher survival rate compared with untreated controls (60% for animals that received 3 × 10 10 plaque forming units; 70% for animals that received 3 × 10 11 plaque forming units; 0% for controls; p < 0.01 for each treatment versus untreated). Surviving animals that received aerophage prophylaxis had fewer methicillin-resistant S. aureus in the lungs compared with untreated control animals that succumbed to pneumonia (1.6 × 10 6 colony forming units/g vs 8.0 × 10 8 ; p < 0.01). Conclusions: Prophylactically administered nebulized bacteriophages reduced lung bacterial burdens and improved survival of methicillin-resistant S. aureus infected rats, underscoring its potential in the context of ventilator-associated pneumonia. Abstract : Supplemental Digital Content is available in the text.